2012
DOI: 10.1371/journal.pone.0041506
|View full text |Cite
|
Sign up to set email alerts
|

Neuronal Transcription Factors Induce Conversion of Human Glioma Cells to Neurons and Inhibit Tumorigenesis

Abstract: Recent findings have demonstrated that the overexpression of lineage-specific transcription factors induces cell fate changes among diverse cell types. For example, neurons can be generated from mouse and human fibroblasts. It is well known that neurons are terminally differentiated cells that do not divide. Therefore, we consider how to induce glioma cells to become neurons by introducing transcription factors. Here, we describe the efficient generation of induced neuronal (iN) cells from glioma cells by the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
42
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(45 citation statements)
references
References 29 publications
3
42
0
Order By: Relevance
“…We also found that transient expression of Ngn2 (by a non-donor episomal plasmid) in radial glia was sufficient to produce ATRT like tumors. The effectiveness of transient Ngn2 expression, in combination with previous findings that Ngn2 or NeuroD1 expressed in glioma cells induces cell death and neuronal differentiation without changing tumor type (46, 47) supports the idea that Ngn2 and NeuroD1 acts in early stage radial progenitors to change the type of tumor generated. We have co-expressed Ngn2 with GFAP donor plasmids and found the resulted tumors were similar to tumors induced by GFAP donor plasmids alone.…”
Section: Discussionsupporting
confidence: 79%
“…We also found that transient expression of Ngn2 (by a non-donor episomal plasmid) in radial glia was sufficient to produce ATRT like tumors. The effectiveness of transient Ngn2 expression, in combination with previous findings that Ngn2 or NeuroD1 expressed in glioma cells induces cell death and neuronal differentiation without changing tumor type (46, 47) supports the idea that Ngn2 and NeuroD1 acts in early stage radial progenitors to change the type of tumor generated. We have co-expressed Ngn2 with GFAP donor plasmids and found the resulted tumors were similar to tumors induced by GFAP donor plasmids alone.…”
Section: Discussionsupporting
confidence: 79%
“…The prognosis of patients with glioma remains poor despite improved treatment modalities, including maximum surgical resection, chemotherapy with anti-neoplastic drugs and radiotherapy 2,3 . Temozolomide (TMZ), an alkylating agent, has shown promising results in the treatment of newly diagnosed patients with glioblastoma multiforme or refractory anaplastic astrocytoma when used as single agent as well as in combination with radiation therapy 4 .…”
Section: Introductionmentioning
confidence: 99%
“…The tumors still grew after 30 days, and tumors from Si-MEK2-infected cells were smaller than those from Si-ctl-infected cells. The mean tumor burden of Si-ctl-infected cells was 125.75 6 114 mm3 (n 5 8) and of Si-MEK2-infected cells was 10.32 6 2.65 mm 3 (n 5 8, P 5 0.013 vs. Si-ctl) (Figure 6e). The function of MEK2 in glioma cell growth.…”
mentioning
confidence: 96%
“…Registration of the two locations within the glioma with predetermined Cho/Cr ratios was carried out as previously described 20. Tumor samples were obtained by experienced neurosurgeons following standard procedures 21. Specimens from each location were divided and immediately sent for neurosphere culture and histopathological evaluation.…”
Section: Methodsmentioning
confidence: 99%